OBSERVATIONS ON THE CHAETOGNATHA OF THE WATERS AROUND MANDAPAM - Sudarsan, D (Indian Journal of Fisheries, 2011)
DIFFERENT species of organisms belonging to diverse groups hke diatoms,medusae, pteropods, chaetognaths and tunicates that occur in the planktonare known to be indicators of the water-masses and changing hydrologicalconditions and of those, chaetognaths have been successfully used in manyregions during recent times. Further, the chaetognaths take their place inthe food cycle of the sea as predators, competitors and prey in relation to theother constituents of the marine animal community and hence the importanceof their study cannot be overemphasised